2015
DOI: 10.1037/pag0000038
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in experiential and deliberative processes in unambiguous and ambiguous decision making.

Abstract: Older adults experience declines in deliberative decisional capacities, while their affective or experiential abilities tend to remain intact (Peters & Bruine de Bruin, 2012). The current study used this framework to investigate age differences in description-based and experience-based decision-making tasks. Description-based tasks emphasize deliberative processing by allowing decision makers to analyze explicit descriptions of choice-reward information. Experience-based tasks emphasize affective or experienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 69 publications
2
25
0
1
Order By: Relevance
“…Studies of value processing that take into account on one's feelings and preferences for choice parameters find little or no evidence of age differences, while studies that place greater requirements on deliberative processing of explicit choice parameters tend to find evidence of age‐related decline. This pattern in consistent with a general shift from deliberative to intuitive/affective processing in aging (Huang et al, ; Mikels et al, ; Peters & Bruine de Bruin, ).…”
Section: Valuation and Choicesupporting
confidence: 80%
See 1 more Smart Citation
“…Studies of value processing that take into account on one's feelings and preferences for choice parameters find little or no evidence of age differences, while studies that place greater requirements on deliberative processing of explicit choice parameters tend to find evidence of age‐related decline. This pattern in consistent with a general shift from deliberative to intuitive/affective processing in aging (Huang et al, ; Mikels et al, ; Peters & Bruine de Bruin, ).…”
Section: Valuation and Choicesupporting
confidence: 80%
“…Many of these theories are built around research indicating that normal aging (implicitly, brain aging) causes selective declines in “fluid cognitive abilities” (a.k.a., deliberative functions; for example, processing speed, working memory, executive functioning; Horn & Cattell, ; Park & Schwarz, ; Peters, Hess, Västfjäll, & Auman, ; Salthouse, ; Schaie & Willis, ), while allowing for relative preservation or growth in “crystallized cognitive abilities” (knowledge; Horn & Cattell, ; Park & Schwarz, ; Salthouse, ; Schaie & Willis, ). In addition, normal aging has been associated with maintenance of affective skills (“affective resiliency”) and an increased prioritization of social and emotional goals (Carstensen et al, ) which can lead to selective processing of affective information (“affective enhancement”; Peters et al, ), increased efforts to regulate emotional states (Kryla‐Lighthall & Mather, ), and an increased reliance on affective/intuitive processing relative to deliberative processing (Huang, Wood, Berger, & Hanoch, ; Mikels, Cheung, Cone, & Gilovich, ; Peters & Bruine de Bruin, ). For example, the affect–integration–motivation (AIM) framework (Samanez‐Larkin & Knutson, 2015) describes how brain aging, preserved crystallized abilities, age‐related changes to affective goals may intersect to impact decision behavior in a context‐dependent manner.…”
Section: Current Theories Of Age‐related Changes To Decision‐makingmentioning
confidence: 99%
“…During healthy ageing, specific (verbatim) representations of memory decay faster and are less accessible than gist representations, and as such, older adults' increased gist reasoning in false‐recall experiments has been linked to this decay in their neurocognitive functioning (e.g., Brainerd & Reyna, ; Koustaal et al, ). In addition, Corbin et al () found that individuals with higher working memory capacity show a preference for gist reasoning strategies in risky decision making, and Huang, Wood, Berger, and Hanoch () have shown that a greater age effect exists when participants make decisions on deliberative tasks compared with experiential tasks. Therefore, it is possible that increases in, and preferences for, gist reasoning emerge via a process of increased life experience alongside reduced cognitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, we should bear in mind that in the results of psychoacoustic studies depend not only on auditory system performance, but also on processing steps, such as attention and decision-making, which are also affected by aging (Füllgrabe et al, 2014;Huang et al, 2015;Strough et al, 2015). The deficits in psychoacoustic tasks observed in humans may be due to a decline of attentional and cognitive abilities (review in Fullgrabe et al 2014).…”
Section: Relationship With Psychoacoustic Datamentioning
confidence: 99%